Aperiodic parameters of the fMRI power spectrum associate with preterm birth and neonatal age - Suuronen, Ilkka; Luotonen, Silja; Railo, Henry; Airola, Antti; Bano, Wajiha; Merisaari, Harri; Pulli, Elmo P.; Mariani Wigley, Isabella L. C.; Vartiainen, Elena; Hashempour, Niloofar; Karlsson, Hasse; Karlsson, Linnea; et al. (Springer Nature, 2026)
Perinatal period is a critical time for brain development and premature-born children have an elevated likelihood for neurodevelopmental conditions. While strong associations of structural magnetic resonance imaging with preterm birth and post-menstrual age (PMA) have been reported, results with functional MRI (fMRI) have been considerably weaker. Using the task-free neonatal fMRI dataset from the Developing Human Connectome Project (dHCP), we first studied the associations of the aperiodic component of the blood-oxygen-level-dependent (BOLD) signal power spectrum from pre- and postcentral gyri with preterm birth and mapped the associations with PMA, postnatal age, and sex, and found clear differences between preterm and full-term groups, as well as males and females. Second, we used machine learning regression to predict participants’ age from the aperiodic parameters of the BOLD signal from 90 cortical and subcortical regions of interest with relatively high accuracy (test R2’s 0.20–0.41).